If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 = 4d Solving 52 = 4d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4d' to each side of the equation. 52 + -4d = 4d + -4d Combine like terms: 4d + -4d = 0 52 + -4d = 0 Add '-52' to each side of the equation. 52 + -52 + -4d = 0 + -52 Combine like terms: 52 + -52 = 0 0 + -4d = 0 + -52 -4d = 0 + -52 Combine like terms: 0 + -52 = -52 -4d = -52 Divide each side by '-4'. d = 13 Simplifying d = 13
| 60=5y | | 5(-2n+4)= | | (-8)+2+1= | | 8.6=n+2.2 | | 27=3x-15+18 | | -5(x-2)+3x=10-4(2x-5)+6 | | 2/11n=-3/8 | | 3x-3=3(x+1)+6 | | X+3x/120 | | 2m-3=-8m+27 | | x^4-2x^3+15x^2=0 | | -1-5x=-36 | | Z+5=8 | | 20-13=20+9x | | 1.3+0.5x=-3.14 | | 8^2+9(12/3*2)-7 | | 16/8=n/36 | | (3)(2)/2-4 | | -6x+1=7-6x | | 153/24 | | 9(v+1)-3v=2(3v+1)-5 | | 1.3c=3c+2.8 | | B-8+6b=24 | | 3(x-3)=6x-18/2 | | 5(2.4-4)=8 | | 568-507x=567 | | 4(-15)=13-6(4) | | -7(7x+6)-3(x-9)= | | 7=-5+6(-8x+2) | | -11=3x+7-3x | | 5y-11-2y^9=0 | | 25x-3=35x+3 |